The Sensitivity Of Ciprofloxacin And Amoxicillin To Bacteria That Cause Chronic Tonsillitis In West Of Nusa Tenggara Provincial Hospital - Diani Sri Hidayati; Nurrahmawati, Nurrahmawati (Sean Institute, 2024)
Chronic tonsillitis is a condition of enlargement tonsil and accompanied by repeated infections. Chronic tonsillitis is most commonly caused by Gram-positive bacteria such as Staphylococcus aureus. Provision of broad-spectrum antibiotics such as Ciprofloxacin and Amoxicillin is able to inhibit the growth of aerobic bacterias that cause chronic tonsillitis.The main objective of this study is to determaine the comparison of Ciprofloxacin and Amoxicillin sensitivity against bacterias causes of chronic tonsillitis Departement of West Nusa Tenggara General Hospital. The design of this study is observation study with cross sectional approach. Forty-nine people with chronic tonsillitis had a throat swab. The sensitivity test was examined by dilution methods for Ciprofloxacin and Amoxicillin antibiotics. The result of the study was analyzed by Chi Square (X2) test with a significance level of p value <0.05. The 49 chronic tonsilitis patients who had throat swab, the most common cause of chronic tonsillitis was Staphylococcus aureus 36 isolates (73,5%). Sensitivity to ciprofloxacin was 41 isolates (83,7%) with an inhibitory zone 28 mm and sensitivity to amoxicillin was 8 isolates (16,3%) %) with an inhibitory zone 20 mm, Ciprofloxacin is more sensitive than Amoxicillin (p<0,05). Ciprofloxacin was more sensitive to bacterias that cause chronic tonsillitis.